واقع برامج الصحة المدرسية المتبعة أثناء تفشي جائحة كورونا "كوفيد19" (El-Wahat Journal for Research and Studies, 2023)
ملخص: نهدف من خلال هدا المقال إلى تحديد واقع برامج الصحة المدرسية، المنتهجة أثناء تفشي جائحة كورونا "كوفيد19" بالمؤسسات التعليمية بالجزائر، وقياس مدى تطبيقاتها على أرض الواقع، بيد أن المدرسة الابتدائية الجزائرية تعد من ضمن المؤسسات التربوية التعليمية، التي تسعى إلى مواكبة الصحة وتطويرها، والاهتمام بها، فمن الضروري تخطيط برنامج يشمل في مقدمته تطوير الناحية الصحية، وذلك لحماية التلاميذ من الأمراض، خاصة مع انتشار وباء كورونا، وعليه سعينا إلى توضيح أهمية برامج الصحة المدرسية المنتهجة في ظل الجائحة، وفي سبيل ذلك قمنا بدراسة نظرية تحليلية، وخلصنا إلى أن المدارس الابتدائية تطبق مجموعة من البرامج والخدمات، والأنظمة، بقصد تعزيز الوضع الصحي في المدارس. ورفع مستوى الوعي الصحي والبيئي للتلاميذ والمعلمين، ورفع مستوى النظافة الشخصية، وتحسين الوضع الصحي والغذائي، والعمل على تحسين خدمات الصحة المدرسية، هذا التطبيق الذي لعب دوراً فعالاً في حماية الأطفال داخل المحيط المدرسي، واكتسابهم لثقافة صحية جيدة لمواجهة وباء  كورونا.كلمات دالة: البرامج الصحية، الصحة المدرسية "كوفيد 19"، المدرسة الابتدائية.   Abstract: Through this article, we aim to determine the reality of school health programs implemented during the outbreak of the Corona pandemic "Covid-19” in educational institutions in Algeria, and to measure the extent of their applications on the ground. And taking care of it, it is necessary to plan a program that includes, foremost, the development of the health aspect, in order to protect students from diseases, especially with the spread of the Corona epidemic, and accordingly we sought to clarify the importance of school health programs implemented in light of the pandemic, and for this we did an analytical theoretical study, and we concluded that primary schools implement a range of programs, services, and systems, with the intent of promoting health status in schools. And raising the level of health and environmental awareness for students and teachers, raising the level of personal hygiene, improving the health and nutritional situation, and working to improve school health services, this application that played an effective role in protecting children within the school environment, and their acquisition of a good health culture to confront the Corona epidemic. Key words: health programs, school health, Covid-19, primary school.